Fair-faced concrete and preparation method thereof
The admixture is prepared by combining activated magnesium carbonate with calcium carbonate sintered with specific ratios of cement, mixed sand, silica fume, fly ash and fiber materials, which solves the problem of insufficient seepage resistance and strength of clean water concrete, and achieves high-performance and low-cost concrete preparation, improving construction simplicity and durability.
Patent Information
- Application Number
- CN202510483277.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-18
AI Technical Summary
The seepage resistance and strength of existing clean water concrete cannot meet high standards, and it has high production costs, high construction complexity, poor long-term stability and reliability, especially in extreme climates.
Admixtures are prepared by activating the sintered magnesium carbonate and calcium carbonate sintered by specific ratios, and the combination of cement, mixed sand, fume, fly ash, fiber materials, admixtures and retarders are used to prepare admixtures by activating the firing of magnesium carbonate and calcium carbonate, increasing the interface binding force and flexible chain segments, and improving the cracking and permeability resistance of concrete.
The prepared concrete has good compressive strength, cracking resistance and permeability, ensuring waterproof performance, better durability, reducing production costs and simplifying the construction process.
Smart Images

Figure BDA0005363402760000031 
Figure BDA0005363402760000041 
Figure BDA0005363402760000061
Abstract
Description
Technical Field
[0001] This application relates to the technical field of concrete materials, and particularly to a fair-faced concrete and a preparation method thereof. Background Art
[0002] In recent years, with the acceleration of the urbanization process, people have put forward higher requirements for the appearance quality of buildings. Due to problems such as rough surface and uneven color of traditional concrete, its extensive application in modern architectural design is restricted to a certain extent. As a new type of building material, fair-faced concrete has gradually gained favor in high-end architectural design due to its smooth and delicate surface and uniform color. However, at present, the impermeability and strength of most fair-faced concrete products on the market cannot meet the high standards of certain specific engineering projects, which has become one of the main bottlenecks restricting its wider popularization and application.
[0003] In order to improve the impermeability and strength of concrete, the commonly adopted technical measures in the industry mainly include adding various modifiers, optimizing the particle size distribution of aggregates, and improving the curing conditions, etc. Among them, adding water-reducing agents can effectively reduce the water consumption of concrete, thereby improving its density and compressive strength; adjusting the proportion and particle size of coarse and fine aggregates helps to reduce the porosity and enhance the overall waterproof effect; in addition, appropriate curing measures are also one of the important factors to ensure the performance of concrete, such as maintaining a wet state by spraying water mist, covering with a moisture-proof film, etc., to promote the full progress of the cement hydration reaction.
[0004] Although the above improvement measures can improve the quality of fair-faced concrete to a certain extent, there are still some problems that cannot be ignored. Firstly, the cost is high, and the prices of many high-performance additives are expensive, increasing the production cost; secondly, the construction complexity increases, and the selection and mixing ratio of raw materials need to be strictly controlled, which is difficult to operate for ordinary construction units; finally, even for the finished products after multiple optimization treatments, their long-term stability and reliability are still difficult to reach the ideal level, especially in extreme climate conditions, cracking, peeling and other phenomena may occur. Summary of the Invention
[0005] In order to solve the above technical problems, this application provides a fair-faced concrete and a preparation method thereof.
[0006] This application provides a fair-faced concrete, which specifically includes the following components in parts by weight: 500 - 580 parts of cement, 800 - 900 parts of mixed sand, 200 - 260 parts of silica fume, 40 - 100 parts of fly ash, 70 - 95 parts of fiber material, 50 - 70 parts of admixture, 5 - 9 parts of retarder, 1 - 5 parts of water-reducing agent, and 180 - 230 parts of water; The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.2 - 1, and calcine at 600 - 700 °C to obtain a calcined product; then mix the calcined product and an activator aqueous solution evenly according to a weight ratio of 1:3 - 5, stir and react at room temperature for 2 - 6 h, then dry at 80 - 120 °C, and then ball mill to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 1,4 - butanediol 30 - 40 g / L, cysteamine hydrochloride 4 - 10 g / L.
[0007] The concrete prepared by using the technical solution of the present application has good workability, the 3d compressive strength is greater than 41 MPa, and the concrete prepared by the present application has good anti - cracking performance and good anti - permeability performance, which ensures the waterproof performance of the concrete and has better durability.
[0008] The admixture provided by the present application is obtained by activating the calcined product of magnesium carbonate and calcium carbonate and then grinding it to increase its specific surface area, thereby improving the interfacial bonding force with the concrete matrix. This activation treatment can make the admixture disperse more evenly in the concrete, effectively fill micro - cracks, and improve the anti - cracking and anti - permeability of the concrete. The calcined product of magnesium carbonate and calcium carbonate activated by 1,4 - butanediol and cysteamine hydrochloride can introduce more flexible chain segments inside the concrete, improve its compatibility with the hydration products in the concrete, enhance the interfacial bonding force, and thus improve the overall performance of the concrete, especially the anti - cracking and anti - permeability performance.
[0009] Preferably, the fair - faced concrete specifically comprises the following components in parts by weight: 520 - 560 parts of cement, 830 - 870 parts of mixed sand, 220 - 240 parts of silica fume, 60 - 80 parts of fly ash, 80 - 90 parts of fiber material, 55 - 65 parts of admixture, 6 - 8 parts of retarder, 2 - 4 parts of water - reducing agent, and 190 - 210 parts of water.
[0010] Preferably, the preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.4 - 0.8, and calcine at 630 - 670 °C for 3 - 5 h to obtain a calcined product; then mix the calcined product and an activator aqueous solution evenly according to a weight ratio of 1:3.5 - 4.5, stir and react at room temperature for 3 - 5 h, then dry at 80 - 120 °C, and then ball mill through a 200 - mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 1,4 - butanediol 33 - 38 g / L, cysteamine hydrochloride 6 - 8 g / L.
[0011] Preferably, the mixed sand is composed of 30 - 50 - mesh quartz sand and 80 - 120 - mesh quartz sand mixed according to a weight ratio of 1 - 5:0.2 - 1.
[0012] Preferably, the mixed sand is composed of quartz sand with a mesh size of 30-50 and quartz sand with a mesh size of 80-120, with a weight ratio of 3-5:0.2-0.5.
[0013] Preferably, the fiber material is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber, basalt fiber, and nylon fiber.
[0014] Preferably, the fiber material is composed of a mixture of polypropylene fibers with a length of 10-20 mm and a length-to-diameter ratio of 30-40 and basalt fibers with a length of 2-8 mm and a length-to-diameter ratio of 40-50, with a weight ratio of 10:0.5-1.5.
[0015] By carefully designing the mixing ratio of the mixed sand and the fiber material, the present application can produce a composite effect and further improve the performance of the concrete.
[0016] Preferably, the silica fume has a particle size of 0.11-0.17 μm and a SiO2 content of ≥88%.
[0017] Preferably, the fly ash is Class F Grade II fly ash, with a fineness of 15.3%, a water demand ratio of 97.2%, and a loss on ignition of 3.6%.
[0018] On the other hand, the present application provides a method for preparing the above fair-faced concrete, which specifically includes the following steps in sequence: weighing the respective raw material components in corresponding weights, adding cement, mixed sand, silica fume, fly ash, and fiber material to water, mixing evenly, then adding admixtures, retarders, and water reducers, stirring and mixing evenly, and through curing, the fair-faced concrete is obtained.
[0019] In summary, the technical solution of the present application has the following effects: The concrete prepared by using the technical solution of the present application has good workability. The concrete prepared by the present application has good compressive strength, anti-cracking performance, and anti-seepage performance, ensuring the waterproof performance of the concrete and having better durability. Specific Embodiments
[0020] The present application will be further described in detail below in combination with examples, comparative examples, and performance detection tests. These examples should not be construed as limiting the scope claimed by the present application. Examples
[0021] Examples 1-3 Examples 1-3 respectively provide a fair-faced concrete and a method for preparing the same.
[0022] The differences between the above examples are as follows: the dosages of the components in the fair-faced concrete are different, as specifically shown in Table 1.
[0023] The preparation method of fair-faced concrete in the above embodiments is as follows: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.6, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 35 g / L of 1,4-butanediol and 7 g / L of cysteamine hydrochloride.
[0024] As shown in Table 1, weigh the corresponding weights of each raw material component respectively. Add cement, mixed sand (the mixed sand is composed of 30-50 mesh quartz sand and 80-120 mesh quartz sand mixed according to a weight ratio of 4:0.3), silica fume, fly ash, and fiber material (the fiber material is composed of polypropylene fiber with a length of 10-20 mm and a length-to-diameter ratio of 30-40 and basalt fiber with a length of 2-8 mm and a length-to-diameter ratio of 40-50 mixed according to a weight ratio of 10:1) into water, mix evenly, then add the admixture, sodium gluconate retarder, and HS-209 type polycarboxylate water reducer, stir and mix evenly, and after curing, fair-faced concrete is obtained.
[0025] Table 1 Dosages of each raw material component of fair-faced concrete in Examples 1-3 and Comparative Examples 1-2 Examples 4-9 Examples 4-9 respectively provide a kind of fair-faced concrete and its preparation method.
[0026] The difference between the above embodiments and Example 1 is that: the preparation method of the admixture is different, which is specifically as follows.
[0027] In Example 4: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.2, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 35 g / L of 1,4-butanediol and 5 g / L of cysteamine hydrochloride.
[0028] In Example 5: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:1, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill and pass through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 35 g / L of 1,4-butanediol and 5 g / L of cysteamine hydrochloride.
[0029] In Example 6: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.6, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill and pass through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 30 g / L of 1,4-butanediol and 10 g / L of cysteamine hydrochloride.
[0030] In Example 7: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.6, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill and pass through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 40 g / L of 1,4-butanediol and 5 g / L of cysteamine hydrochloride.
[0031] In Example 8: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.6, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill and pass through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 33 g / L of 1,4-butanediol and 8 g / L of cysteamine hydrochloride.
[0032] In Example 9: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.6, and calcine at 650 °C for 4 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball mill and pass through a 200-mesh sieve to obtain the admixture; the activator aqueous solution is composed of components with the following concentrations: 38 g / L of 1,4-butanediol and 6 g / L of cysteamine hydrochloride.
[0033] In the above examples, other process parameters are the same as those in Example 1.
[0034] Examples 10 - 13 Examples 10 - 13 respectively provide a fair - faced concrete and its preparation method.
[0035] The differences between the above - mentioned examples and Example 1 are as follows: the types of quartz sand are different, as shown below.
[0036] In Example 10: The mixed sand is composed of quartz sand with a mesh size of 10 - 30 and quartz sand with a mesh size of 160 - 200, with a weight ratio of 4:0.3.
[0037] In Example 11: The mixed sand is composed of quartz sand with a mesh size of 30 - 50 and quartz sand with a mesh size of 80 - 120, with a weight ratio of 0.3:4.
[0038] In Example 12: The mixed sand is composed of quartz sand with a mesh size of 30 - 50 and quartz sand with a mesh size of 80 - 120, with a weight ratio of 1:1.
[0039] In Example 13: The mixed sand is composed of quartz sand with a mesh size of 30 - 50 and quartz sand with a mesh size of 80 - 120, with a weight ratio of 5:0.2.
[0040] The differences between the above - mentioned examples and Example 1 are specifically as follows: Different, specifically: In the above - mentioned examples, other process parameters are the same as those in Example 1.
[0041] Examples 14 - 17 Examples 14 - 17 respectively provide a fair - faced concrete and its preparation method.
[0042] The differences between the above - mentioned examples and Example 1 are as follows: the preparation methods of the admixtures are different, as shown below.
[0043] In Example 14: The fiber material is composed of polyvinyl alcohol fibers with a length of 10 - 20 mm and a length - to - diameter ratio of 30 - 40 and nylon fibers with a length of 2 - 8 mm and a length - to - diameter ratio of 40 - 50, with a weight ratio of 10:1.
[0044] In Example 15: The fiber material is composed of polypropylene fibers with a length of 10 - 20 mm and a length - to - diameter ratio of 30 - 40 and basalt fibers with a length of 2 - 8 mm and a length - to - diameter ratio of 40 - 50, with a weight ratio of 1:10.
[0045] In Example 16: The fiber material is composed of polypropylene fibers with a length of 10 - 20 mm and a length - to - diameter ratio of 30 - 40 and basalt fibers with a length of 2 - 8 mm and a length - to - diameter ratio of 40 - 50, with a weight ratio of 10:0.5.
[0046] In Example 17: The fiber material is composed of a mixture of polypropylene fibers with a length of 10 - 20 mm and an aspect ratio of 30 - 40 and basalt fibers with a length of 2 - 8 mm and an aspect ratio of 40 - 50, with a weight ratio of 10:1.5.
[0047] In the above examples, other process parameters are the same as those in Example 1.
[0048] Comparative Example Comparative Examples 1 - 2 Comparative Examples 1 - 2 respectively provide a fair - faced concrete and its preparation method.
[0049] The differences between the above - mentioned comparative examples and Example 1 are as follows: The dosages of each component in the fair - faced concrete are different, as shown in Table 1 specifically.
[0050] In the above - mentioned comparative examples, other process parameters are the same as those in Example 1.
[0051] Comparative Examples 3 - 4 Comparative Examples 3 - 4 respectively provide a fair - faced concrete and its preparation method.
[0052] The differences between the above - mentioned comparative examples and Example 1 are as follows: The dosages of each component in the fair - faced concrete are different, as shown in Table 1 specifically.
[0053] In Comparative Example 3: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.6, and calcine at 650 °C for 4 h to obtain the calcined product.
[0054] In Comparative Example 4: The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 0.6:1, and calcine at 650 °C for 4 h to obtain the calcined product; then mix the calcined product with the activator aqueous solution evenly according to a weight ratio of 1:4, stir and react at room temperature for 4 h, then dry at 100 °C, and then ball - mill and pass through a 200 - mesh sieve to obtain the admixture; the activator aqueous solution is composed of the following components at a concentration: 1,4 - butanediol 50 g / L.
[0055] In the above - mentioned comparative examples, other process parameters are the same as those in Example 1.
[0056] Performance Detection Test (1) Compressive strength, splitting tensile strength: The compressive strength and splitting tensile strength of the fair - faced concrete are determined with reference to GB / T50081 - 2019 "Standard Test Method for Mechanical Properties of Ordinary Concrete".
[0057] (2) Chloride ion penetration resistance: The chloride ion penetration depth of the standard specimens of fair - faced concrete is tested by the rapid chloride migration coefficient method in GB / T 50082 "Standard Test Method for Long - Term Performance and Durability of Ordinary Concrete".
[0058] (3) Impermeability water pressure performance: According to the testing method specified in GB / T 50082-2009, install the sealed fair-faced concrete specimens on the impermeability tester. Start the test with a water pressure of 0.1 MPa, increase the water pressure by 0.01 MPa every 1 h, and pay attention to observing the end face situation of the specimens at any time. Record the water leakage situation and the corresponding pressure of the specimen end face respectively to detect the impermeability pressure of the fair-faced concrete.
[0059] Test results: As shown in Table 2.
[0060] Table 2 Test results of fair-faced concrete in the examples and comparative examples Combined with Table 2, by comparing the performance test results of the fair-faced concrete in the examples and comparative examples, it can be seen that the concrete prepared by using the technical solution of the present application has good workability, the 3d compressive strength is greater than 41 MPa, and the concrete prepared by the present application has good anti-cracking performance and good impermeability performance, which ensures the waterproof performance of the concrete and has better durability.
[0061] In Comparative Examples 1-2, the raw material ratios of the components of the concrete do not match, and the performance of the prepared concrete is poor; in Comparative Example 3, the fired product of magnesium carbonate and calcium carbonate is directly used as an admixture, and in Comparative Example 4, the ratio of magnesium carbonate and calcium carbonate does not match, and the activator aqueous solution is 1,4-butanediol aqueous solution, and the performance of the prepared concrete is poor.
[0062] In contrast, the present application uses 1,4-butanediol and cysteamine hydrochloride with specific concentrations as activators to activate the fired product of magnesium carbonate and calcium carbonate, and matches it with other raw materials in specific amounts, and the prepared concrete has good performance.
[0063] Although the present invention has been described in detail above with general descriptions and specific embodiments, based on the present invention, some modifications or improvements can be made, which are obvious to those skilled in the art. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope claimed by the present invention.
Claims
1. A fair-faced concrete, characterized in that, Specifically, it includes the following components in parts by weight: 500 - 580 parts of cement, 800 - 900 parts of mixed sand, 200 - 260 parts of silica fume, 40 - 100 parts of fly ash, 70 - 95 parts of fiber material, 50 - 70 parts of admixture, 5 - 9 parts of retarder, 1 - 5 parts of water reducer, and 180 - 230 parts of water; The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.2 - 1, and calcine at 600 - 700 °C to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:3 - 5, stir and react at room temperature for 2 - 6 h, then dry at 80 - 120 °C, and then ball mill to obtain the admixture; the activator aqueous solution consists of the following components in concentration: 30 - 40 g / L of 1,4 - butanediol, 4 - 10 g / L of cysteamine hydrochloride.
2. The fair-faced concrete according to claim 1, wherein, Specifically, it includes the following components in parts by weight: 520 - 560 parts of cement, 830 - 870 parts of mixed sand, 220 - 240 parts of silica fume, 60 - 80 parts of fly ash, 80 - 90 parts of fiber material, 55 - 65 parts of admixture, 6 - 8 parts of retarder, 2 - 4 parts of water reducer, and 190 - 210 parts of water.
3. The fair-faced concrete according to claim 1, characterized in that, The preparation method of the admixture is as follows: Mix magnesium carbonate and calcium carbonate evenly according to a weight ratio of 1:0.4 - 0.8, and calcine at 630 - 670 °C for 3 - 5 h to obtain a calcined product; then mix the calcined product with an activator aqueous solution evenly according to a weight ratio of 1:3.5 - 4.5, stir and react at room temperature for 3 - 5 h, then dry at 80 - 120 °C, and then ball mill through a 200 - mesh sieve to obtain the admixture; the activator aqueous solution consists of the following components in concentration: 33 - 38 g / L of 1,4 - butanediol, 6 - 8 g / L of cysteamine hydrochloride.
4. The fair-faced concrete according to claim 1, characterized in that, The mixed sand is composed of 30 - 50 - mesh quartz sand and 80 - 120 - mesh quartz sand mixed in a weight ratio of 1 - 5:0.2 - 1.
5. The fair-faced concrete according to claim 1, wherein The mixed sand is composed of 30 - 50 - mesh quartz sand and 80 - 120 - mesh quartz sand mixed in a weight ratio of 3 - 5:0.2 - 0.
5.
6. The fair-faced concrete according to claim 1, characterized in that, The fiber material is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber, basalt fiber, and nylon fiber.
7. The fair-faced concrete according to claim 6, wherein The fiber material is composed of polypropylene fiber with a length of 10 - 20 mm and a length - to - diameter ratio of 30 - 40 and basalt fiber with a length of 2 - 8 mm and a length - to - diameter ratio of 40 - 50 mixed in a weight ratio of 10:0.5 - 1.
5.
8. The fair-faced concrete according to claim 1, characterized in that, The particle size of the silica fume is 0.11 - 0.17 μm, and the SiO2 content ≥ 88%.
9. The fair-faced concrete according to claim 1, wherein The fly ash is Class F Grade II fly ash, with a fineness of 15.3%, a water demand ratio of 97.2%, and a loss on ignition of 3.6%.
10. The preparation method of fair-faced concrete according to any one of claims 1-9, characterized in that, Specifically, it includes the following steps carried out in sequence: Weigh the respective raw material components, add cement, mixed sand, silica fume, fly ash, and fiber material to water, mix evenly, then add the admixture, retarder, and water reducer, stir and mix evenly, and after curing, the fair - faced concrete is obtained.